2021
DOI: 10.2147/jaa.s332245
|View full text |Cite
|
Sign up to set email alerts
|

Type 2-High Severe Asthma with and without Bronchiectasis: A Prospective Observational Multicentre Study

Abstract: Introduction: Type 2-high severe asthma (T2-SA) is often associated with several comorbidities. To this extent, the coexistence of T2-SA and bronchiectasis (BE) is considered an emerging phenotype. Methods: We performed a prospective observational multicentre study, including T2-SA patients. Chest HRCT confirmed the presence of BE. Data on exacerbations, pulmonary function, Asthma Control Test (ACT), chronic mucus hypersecretion (CMH), chronic rhinosinusitis (CRS), oral corticosteroid (OCS) dosage, eosinophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 61 publications
0
22
0
1
Order By: Relevance
“…Importantly, mucus plug and mucus hypersecretion are strongly associated with severe eosinophilic asthma (Dunican et al, 2018). Also, these manifestations are often accompanied with bronchiectasis with chronic airflow obstruction in severe asthma (Crimi et al, 2021). Thus, EETosis may be an optimal therapeutic target in refractory eosinophilic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, mucus plug and mucus hypersecretion are strongly associated with severe eosinophilic asthma (Dunican et al, 2018). Also, these manifestations are often accompanied with bronchiectasis with chronic airflow obstruction in severe asthma (Crimi et al, 2021). Thus, EETosis may be an optimal therapeutic target in refractory eosinophilic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Another important advantage of our study was that we considered comorbidity profiles that might affect the development of bronchiectasis in the analyses of the association of female sex hormones with bronchiectasis. Previous studies have shown that airway diseases such as asthma [ 36 , 37 ], COPD [ 38 ], and pulmonary tuberculosis [ 39 ] are major aetiologies of bronchiectasis. For example, Crimi et al showed a link between asthma and bronchiectasis by demonstrating that a type 2 inflammation could provide a causative role in the development of bronchiectasis [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that airway diseases such as asthma [ 36 , 37 ], COPD [ 38 ], and pulmonary tuberculosis [ 39 ] are major aetiologies of bronchiectasis. For example, Crimi et al showed a link between asthma and bronchiectasis by demonstrating that a type 2 inflammation could provide a causative role in the development of bronchiectasis [ 36 , 37 ]. Additionally, a recent longitudinal study showed that bronchiectasis could develop in subjects with COPD who had bronchial infections; post-tuberculosis bronchiectasis is known to be one of the leading aetiologies of bronchiectasis worldwide [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, experts can personalize treatment based on existing comorbidities before initiating treatment with an mAb CT score and ameliorate patient outcomes. [ 31 ].…”
Section: The Link Between Severe Asthma and Nasal Polypsmentioning
confidence: 99%